Tolerating Violence against Women: Attitude Evolution and Typology in Romania - Cosima Rughiniș; Simona-Nicoleta Vulpe; Răzvan Rughiniș; Daniel Rosner (Sociologie Românească)
In this study, we investigate public attitudes toward violence against women, by analyzing the 2022 Violence Against Women (VaW) survey in Romania. The objectives of this research are to study the evolution of attitudes, to explore the typology of tolerance regarding violence against women, and to uncover the social stratification of the typology of tolerance attitudes in this regard. The methodology uses secondary analysis of a nationally representative survey, using both linear and cluster analysis to explore patterns in public tolerance regarding violence against women. We found that violence against women is strongly condemned by a large majority of the Romanian population, albeit with some variability. Men and people with lower formal education, lower household income, and who are more religiously involved were more likely to express weaker condemnation of violence against women. We identified four types of attitudes through cluster analysis, distinguishing people with zero tolerance from a very small cluster with high tolerance for all forms of violence against women. In addition, two types of relative tolerance were identified, namely the cluster of “tolerance for domestic patriarchalism,” which was discursively inclined toward some justification for social violence and for forms of sexual violence, but not for physical violence, and the cluster of “tolerance for domestic violence,” which was inclined toward some justification for verbal, physical, sexual, and social violence located in the household or between men and women who are familiar which each other. This study contributes to the understanding of how social norms and discursive practices influence gender-related attitudes and the legitimization of violence, with implications for policy and public education aimed at reducing tolerance for gender-based violence.